Colonizações persistentes, modernismos urgentes: a colonização da subjetividade no gênero musical da contemporary worship e a resistência cultural no modernismo - Moret, Geandre Melo (2023)
The current research intends to demonstrate how the majority of the songs used in brazilian evangelical services is historically detached from the nation’s own musical heritage, once they have been connected to Global North structures. The central example of such cultural split, nowadays, is the so-called contemporary worship, which will be studied in its Global North birth, its connection to church growth movements, its importance to American and Australian mega-churches and its traffic to Brazil. The main effect of such silencing of Brazilian artistic culture on evangelicalism will be comprehended in terms of subjectivity colonization, concept which will be historically tracked and understood as a tool not only for the contemporary worship, on the fragment of Brazilian evangelical music, but also on the formation of the first evangelical hymnals – such as the Cantor Cristão, by protestant missionaries from the North. Lastly, as a suggestion of resistance to such gears of subjectivity colonization of the Brazilian evangelical throughout its music, the Modernismo will be rescued, along with its tropicalista derivation, an some examples of Brazilian evangelical musicians who carry a genuinely Brazilian musical repertoire.(AU)